LANGUAGE PREFERENCE USED BY INFORMATION TECHNOLOGY STUDENTS - Ramadhani, Putri (Universitas Methodist Indonesia, 2023)
Language preference is an activity to select a default language for language users. In several activities, we, as language users often found that speakers tend to choose certain language to be used in communication. The objective of this reasearch is is to investigate the preference of language used by Information Technology (IT) students in Budi Darma University Medan in year 2022, which language they prefer to use, Bahasa Indonesia or English? Especially when they learn and discuss about computer or informatioan and techology matter in the classroom or computer laboratory. The participants of this research are fifty (50) EFL learners in Budi Darma who are the native speakers of Indonesian Language which is called Bahasa Indonesia. The researchers would like to find out which language is preferable to be used in the classroom especially when they talk about technology (IT) related to the computer. Piper (1986) popular with “labspeak” term, is there any relation to use certain language rather than other language when the students in computer laboratory? The investigation is done to found out their reasons why they prefer using certain language when they talk about computer and technology (IT) in the classroom. To find the answer, the reasearchers observe and interview the students, the preferable language used by the EFL learners and also reasons of those EFL learners become the finding of this research. The motivations of those students using certain language rather than other language when they talk bout Technology or Information Technology related to computer is also considered esential to support the finding of this research).